Generation and analysis of expressed sequence tags from a cDNA library of the fruiting body of Ganoderma lucidum - Li Xiwen; Li Ying; Lan Jin; Song Jingyuan; Sun Chao; Luo Hongmei; Chen Shilin (BMC, 2010)
Abstract Background Little genomic or trancriptomic information on Ganoderma lucidum (Lingzhi) is known. This study aims to discover the transcripts involved in secondary metabolite biosynthesis and developmental regulation of G. lucidum using an expressed sequence tag (EST) library. Methods A cDNA library was constructed from the G. lucidum fruiting body. Its high-quality ESTs were assembled into unique sequences with contigs and singletons. The unique sequences were annotated according to sequence similarities to genes or proteins available in public databases. The detection of simple sequence repeats (SSRs) was preformed by online analysis. Results A total of 1,023 clones were randomly selected from the G. lucidum library and sequenced, yielding 879 high-quality ESTs. These ESTs showed similarities to a diverse range of genes. The sequences encoding squalene epoxidase (SE) and farnesyl-diphosphate synthase (FPS) were identified in this EST collection. Several candidate genes, such as hydrophobin, MOB2, profilin and PHO84 were detected for the first time in G. lucidum. Thirteen (13) potential SSR-motif microsatellite loci were also identified. Conclusion The present study demonstrates a successful application of EST analysis in the discovery of transcripts involved in the secondary metabolite biosynthesis and the developmental regulation of G. lucidum.